Endogenous Isoquinoline Alkaloids Agonists of Acid-Sensing Ion Channel Type 3 - Osmakov, Dmitry I.; Koshelev, Sergey G.; Andreev, Yaroslav A.; Kozlov, Sergey A. (Frontiers in Molecular Neuroscience, 2017)
Acid-sensing ion channels (ASICs) ASIC3 expressed mainly in peripheral sensory neurons play an important role in pain perception and inflammation development. In response to acidic stimuli, they can generate a unique biphasic current. At physiological pH 7.4, human ASIC3 isoform (hASIC3) is desensitized and able to generate only a sustained current. We found endogenous isoquinoline alkaloids (EIAs), which restore hASIC3 from desensitization and recover the transient component of the current. Similarly, rat ASIC3 isoform (rASIC3) can also be restored from desensitization (at pH < 7.0) by EIAs with the same potency. At physiological pH and above, EIAs at high concentrations were able to effectively activate hASIC3 and rASIC3. Thus, we found first endogenous agonists of ASIC3 channels that could both activate and prevent or reverse desensitization of the channel. The decrease of EIA levels could be suggested as a novel therapeutic strategy for treatment of pain and inflammation.